2012
DOI: 10.1371/journal.pone.0035438
|View full text |Cite
|
Sign up to set email alerts
|

Competitive Reporter Monitored Amplification (CMA) - Quantification of Molecular Targets by Real Time Monitoring of Competitive Reporter Hybridization

Abstract: BackgroundState of the art molecular diagnostic tests are based on the sensitive detection and quantification of nucleic acids. However, currently established diagnostic tests are characterized by elaborate and expensive technical solutions hindering the development of simple, affordable and compact point-of-care molecular tests.Methodology and Principal FindingsThe described competitive reporter monitored amplification allows the simultaneous amplification and quantification of multiple nucleic acid targets b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 37 publications
0
16
0
Order By: Relevance
“…Developers of POC viral load technologies are addressing this challenge either by building in an internal or external plasma separation step or by utilizing a more targeted biomarker. The Alere Q NAT POC assay (Alere Technologies, Jena, Germany) detects HIV-specific RNA and utilizes a smallvolume whole-blood input cartridge (6,7). This technology has recently been evaluated for the diagnosis of HIV in infants under 18 months of age in primary health care clinics, with promising results (8).…”
mentioning
confidence: 99%
“…Developers of POC viral load technologies are addressing this challenge either by building in an internal or external plasma separation step or by utilizing a more targeted biomarker. The Alere Q NAT POC assay (Alere Technologies, Jena, Germany) detects HIV-specific RNA and utilizes a smallvolume whole-blood input cartridge (6,7). This technology has recently been evaluated for the diagnosis of HIV in infants under 18 months of age in primary health care clinics, with promising results (8).…”
mentioning
confidence: 99%
“…After loading the sample capillary with 25 µL of plasma, each cartridge was inserted into an Alere q Analyzer where RNA isolation, cDNA synthesis, PCR and signal detection occur. The Alere q Analyzer reported either “detected” or “not detected” results for HIV-1 Group M/N, HIV-1 Group O and HIV-2 (18). The tests described in this study were carried out using four Alere q Analyzers in the Clinical Laboratory Improvement Amendments (CLIA)-certified and College of American Pathologists (CAP)-accredited UW Clinical Retrovirus laboratory.…”
Section: Methodsmentioning
confidence: 99%
“…The Alere q HIV-1/-2 Detect (Alere Detect) test is a rapid point-of-care (POC) nucleic acid test (NAT) providing several advantageous characteristics for HIV diagnosis: 1) the requirement for only 25 microliters plasma or whole blood per test; 2) test completion within one hour; 3) detection and differentiation of HIV-1 Group M/N, HIV-1 Group O and HIV-2 nucleic acid; and 4) the only currently available POC NAT able to detect HIV-2 (18). Two studies have demonstrated the feasibility of the Alere Detect test to diagnose HIV-1 infection for HIV-1-exposed infants in South Africa and Mozambique (19, 20).…”
Section: Introductionmentioning
confidence: 99%
“…Nucleic acids amplification tests are important tools enabling sensitive, specific, and rapid detection of genetictargets 5 . Of these techniques, real-time polymerase chain reaction (rtPCR) is the basis for a majority of molecular assays 6 .…”
Section: Introductionmentioning
confidence: 99%
“…Microarrays area preferred method for the detection of multiple targets and these tools are expected to become a significant part of clinical diagnostic testing in the future along with next generation nucleotide sequencing methods 9, 10 . A major limitation hampering the implementation of microarrays in clinical setups derives from complex workflow, requiring numerous steps from sample to results 5, 11 . Furthermore, PCR produces double-stranded DNA targets requiring denaturation or preferably digestion of the complementary strand prior to hybridization onto capture probes immobilized on a solid support 12, 13 .…”
Section: Introductionmentioning
confidence: 99%